2017
DOI: 10.3350/cmh.2016.0109
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition in nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease whose prevalence has reached global epidemic proportions. Although the disease is relatively benign in the early stages, when severe clinical forms, including nonalcoholic steatohepatitis (NASH), cirrhosis and even hepatocellular carcinoma, occur, they result in worsening the long-term prognosis. A growing body of evidence indicates that NAFLD develops from a complex process in which many factors, including genetic susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
147
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 193 publications
(156 citation statements)
references
References 76 publications
1
147
0
8
Order By: Relevance
“…In fact, measures of abdominal adiposity may best predict development of severe liver disease in NAFLD . Severity of NAFLD is also driven, in part, by single‐nucleotide polymorphisms in genes involved in lipid metabolism, oxidative stress, insulin signaling, and fibrogenesis . Genetic polymorphisms in the patatin‐like phospholipase domain‐containing‐3 ( PNPLA3 ) gene, which is related to lipid transformation, is now recognized as the major common genetic determinant of NAFLD and is associated with progression to nonalcoholic steatohepatitis (NASH) in both lean and obese NAFLD .…”
mentioning
confidence: 99%
“…In fact, measures of abdominal adiposity may best predict development of severe liver disease in NAFLD . Severity of NAFLD is also driven, in part, by single‐nucleotide polymorphisms in genes involved in lipid metabolism, oxidative stress, insulin signaling, and fibrogenesis . Genetic polymorphisms in the patatin‐like phospholipase domain‐containing‐3 ( PNPLA3 ) gene, which is related to lipid transformation, is now recognized as the major common genetic determinant of NAFLD and is associated with progression to nonalcoholic steatohepatitis (NASH) in both lean and obese NAFLD .…”
mentioning
confidence: 99%
“…PNPLA3 and TM6SF2 variants lower triglyceride levels by decreasing intrahepatic lipolysis, thereby promoting hepatic fat storage. These variants are associated with a distinct form of NAFLD that may also co‐exist with insulin resistance . Although, PNPLA3 , TM6SF2 and GCK genes have shown the strongest associations with NAFLD in GWAS, accounting for 10% of heritability, multiple genes with small additive effects are also causative .…”
Section: Obesity and Cardiometabolic Risk Phenotypesmentioning
confidence: 99%
“…These variants are associated with a distinct form of NAFLD that may also co‐exist with insulin resistance . Although, PNPLA3 , TM6SF2 and GCK genes have shown the strongest associations with NAFLD in GWAS, accounting for 10% of heritability, multiple genes with small additive effects are also causative . A GWAS of 2111 participants in the Dallas Heart Study revealed a robust association of liver fat defined by magnetic spectroscopy with the I148M allele of the PNPLA3 gene; this association was independently replicated in children and adolescents .…”
Section: Obesity and Cardiometabolic Risk Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the genetic component of nonalcoholic fatty liver disease (NAFLD) has significantly contributed to the understanding of the disease pathogenesis. Genetic studies based either on genome‐wide association strategies or candidate gene approaches showed that variants in loci involved in lipid metabolism and/or lipid‐droplet biology have predominant and reproducible effects on the disease phenotype . However, it has been a major challenge to translate this information into molecularly plausible and clinically safe therapeutic targets.…”
mentioning
confidence: 99%